Working with the past : towards an archaeology of recycling - Gheorgiu, Dragoş; Mason, Phil (Access archaeology., 2017)
Recycling is a basic anthropological process of humankind. The reutilization of materials or of ideas from the past is a process determined by various natural or cultural causes. Recycling can be motivated by a crisis or by a complex symbolic cause like the incorporation of the past into the present. What archaeology has not insisted upon is the dimensional scale of the process, which operates from the micro-scale of the recycling of the ancestors' material, up to the macro-scale of the landscape. It is well known that there are direct relations between artefacts and landscapes in what concerns the materiality and mobility of objects. An additional relation between artefact and landscape may be the process of recycling. In many ways artefact and landscape can be considered as one aspect of material culture, perceived at a different scale, since both have the same materiality and suffer the same process of reutilisation.